2019
DOI: 10.21608/edj.2019.72822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Surface Treatment Modalities on Surface Roughness and Shear Bond Strength of Orthodontic Molar Tubes to Lithium Disilicate Ceramics

Abstract: Objectives; This study aimed to evaluate the effect of different surface treatment modalities on surface roughness(SR) and shear bond strength (SBS) of orthodontic molar tubes to lithium disilicate (IPS e-max CAD/CAM, Ivoclar Vivadent) ceramic and human enamel using different adhesives. Materials and methods:A total of 150 e-max specimens were randomly divided into five groups (n=30) according to the method of surface treatment used. In group I (control group): no surface treatment, group II: sandblasting with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…20, 23-27. The greater surface area and higher surface roughness induced by the usual way of surface treatment can explain the rise in bond strength values when utilising an etching step with HF+S. Rania and Bayoumi (2019) 28 The surface roughness of lithium disilicate and SBS were shown to have a substantial positive association, according to their study.…”
Section: Mep (Monobond Etch and Primementioning
confidence: 92%
“…20, 23-27. The greater surface area and higher surface roughness induced by the usual way of surface treatment can explain the rise in bond strength values when utilising an etching step with HF+S. Rania and Bayoumi (2019) 28 The surface roughness of lithium disilicate and SBS were shown to have a substantial positive association, according to their study.…”
Section: Mep (Monobond Etch and Primementioning
confidence: 92%
“…Mechanical roughening can be performed by air abrasion or using a diamond bur. On the other hand, chemical roughening includes the application of hydrofluoric acid (HFA) and phosphoric acid (PhA), followed by silane coupling agents [16][17][18][19]. Sundfeld et al and Garboza et al showed that etching lithium disilicate ceramics with 10% HFA for 20 s with subsequent silane application resulted in high bond strengths [20,21].…”
Section: Manufacturing Technologies Allow It To Have Both High Perfor...mentioning
confidence: 99%
“…Currently, with the availability of multiple types of aesthetic restorations and bonding techniques, orthodontists are facing challenges in determining the best methods in surface conditioning and bonding procedures to ceramics that makes a good attachments bond and that does not affect the ceramic's surface after debonding [13,19]. Moreover, choosing the best composite type to produce durable attachments is considered another challenge.…”
Section: Manufacturing Technologies Allow It To Have Both High Perfor...mentioning
confidence: 99%
See 2 more Smart Citations